Influence of citral on acrylamide formation in model systems. (1st June 2022) - Zhu, Yuchen; Xu, Ruimin; Luo, Yinghua; Sun, Guoyu; Lin, Mengyi; Hu, Xiaosong; Chen, Fang
Highlights: Cit significantly enhanced the formation of AA in a dose-dependent manner. Cit rather than its oxidation product played a major role in the formation of AA. Cit directly reacted with Asn via the Maillard reaction producing AA. Cit promoted the formation of AA between Asn and Glc. Abstract: This work aimed to evaluate the role of citral (Cit) in the formation of acrylamide (AA) in model systems. The asparagine (Asn)/glucose (Glc), Asn/Glc/ginger essential oil (GEO), and Asn/Glc/Cit model systems were prepared and analysed by UPLC-MS/MS. Cit was implicated to be a major product that contributed to the enhancement of AA formation by GEO. The addition of Cit significantly enhanced the formation of AA in the Asn/Glc model system in a dose-dependent manner. Further analysis showed Cit rather than its oxidation product played a major role in AA formation. Cit not only directly reacted with Asn via the Maillard reaction producing AA but also promoted the formation of AA between Asn and Glc.